On-Body Performance of a Frequency Reconfigurable Wearable Antenna for 5G Health Monitoring Application (ELEKTRIKA- Journal of Electrical Engineering, 2022)
This paper presents the design and simulation of a meandered bowtie frequency reconfigurable wearable antenna for a 5G health monitoring application. The antenna is based on a transdermal patch as the substrate, hence it offers convenience when it is applied on a user as compared to other recent developed wearable antennas. The antenna can cater to various frequencies especially the 5G frequency bands in Malaysia (700MHz, 3.5GHz) and Indonesia (2.3 GHz, 3.4 - 3.6 GHz). Studies on the deployment of the antenna on a body phantom are also presented in this paper as well as several techniques to reduce the on-body effects. Results have shown that the design can be a promising candidate in wearable healthcare monitoring applications as well as a reference for future research and studies.